2019
DOI: 10.1111/jhn.12633
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated and decaffeinated coffee consumption and risk of all‐cause mortality: a dose–response meta‐analysis of cohort studies

Abstract: Background Previous meta‐analysis showed an inverse association between coffee consumption and all‐cause mortality. However, the relationship between caffeinated and decaffeinated coffee consumption and all‐cause mortality is inconsistent. We aimed to identify and review the published evidence updating the association between coffee consumption and all‐cause mortality and, furthermore, to investigate the association of caffeinated and decaffeinated coffee consumption and all‐cause mortality. Methods We systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 57 publications
2
16
0
1
Order By: Relevance
“…This is the conclusion of an umbrella review of meta-analyses of multiple health outcomes, even after extensive correction for a large number of possible confounding factors [1], and also the result of the EPIC (European Prospective Investigation into Cancer and Nutrition Study) trial analyzing coffee consumption versus mortality [2]. Consumption of decaffeinated coffee was associated with similar beneficial outcomes, but only if data of large cohorts were available [3][4][5]. The molecular mechanism responsible for these putative health effects is still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…This is the conclusion of an umbrella review of meta-analyses of multiple health outcomes, even after extensive correction for a large number of possible confounding factors [1], and also the result of the EPIC (European Prospective Investigation into Cancer and Nutrition Study) trial analyzing coffee consumption versus mortality [2]. Consumption of decaffeinated coffee was associated with similar beneficial outcomes, but only if data of large cohorts were available [3][4][5]. The molecular mechanism responsible for these putative health effects is still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most striking effect of coffee intake is the ability to increase lifespan and, most importantly, healthspan on ageing [ 106 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ], as concluded from the analysis of different cohorts in Europe [ 158 , 159 , 160 , 161 , 162 , 163 , 164 ], America [ 165 , 166 , 167 ], and Asia [ 168 , 169 , 170 , 171 ], with different ethnicities [ 170 ] and different types of coffee [ 167 ]; these effects were observed similarly in both men and women [ 152 , 161 ] with different polymorphisms [ 162 , 172 ], sharply contrasting with the positive association of life-long acrylamide exposure [ 173 ] and acrylamide–hemoglobin adducts [ 174 ] with mortality.…”
Section: Other General Beneficial Health Effects Of Coffeementioning
confidence: 99%
“…Habitual coffee drinkers will experience less of this blood pressure rising effect due to increased tolerance of caffeine [37]. A recent meta-analysis that looked at both caffeinated and decaffeinated coffee consumption and all-cause mortality found no difference in the risk reduction (per 1 cup/day increments) from all-cause mortality between caffeinated and decaffeinated coffee [20]. This indicates that the effect of coffee on all-cause mortality might be unrelated to the caffeine consumption.…”
Section: Cardiovascular Mortalitymentioning
confidence: 99%
“…To this day, there are several meta-analyses conducted in order to quantify the risk of overall and cause specific mortality in regards to coffee consumption [ 17 20 ]. The results from the meta-analyses all indicated that coffee consumption was associated with a lower risk of all-cause mortality, and in two meta-analyses, coffee consumption reduced the risk of mortality from cardiovascular diseases (CVD).…”
Section: Introductionmentioning
confidence: 99%